The contributions of NMDA, non-NMDA, and GABA receptors to postsynaptic responses in neurons of the optic tectum - Hickmott, PW (J Neurosci, 1993)
Activation of the NMDA subtype of glutamate receptor has been implicated in activity-dependent development and plasticity in several systems, including the retinotectal system of amphibians. To gain a better understanding of the response properties of tectal neurons, with particular emphasis on the role of both non-NMDA and NMDA glutamate receptors, we have developed an in vitro slice preparation of the diencephalon and midbrain of frog (Rana pipiens) tadpoles. In these slices, we electrically stimulated the optic tract and recorded both mono- and polysynaptic responses in single tectal neurons using whole- cell voltage clamp or current clamp. By including biocytin in the recording electrode, we were also able to determine the location and morphology of many of these neurons. Using these techniques, we found that the current-voltage (I-V) relations for both mono- and polysynaptic responses of tectal neurons showed voltage dependence only in the presence of extracellular Mg2+. This dependence reflects the hyperpolarization-dependent block of the NMDA channel by Mg2+. Bath application of 6-cyano-7-nitroquinoxaline-2,3-dione, a non-NMDA glutamate receptor antagonist, reduced both mono- and polysynaptic responses of tectal neurons. Bath application of the NMDA receptor antagonist DL-2-amino-5-phosphonovaleric acid (DL-APV) strongly reduced polysynaptic responses. When neurons were depolarized by the voltage clamp, relieving the Mg(2+)-dependent block of the NMDA channel, DL-APV application also reduced monosynaptic responses. Application of the GABAA receptor antagonist (-)bicuculline methiodide significantly increased the polysynaptic responses of tectal neurons, reflecting block of inhibition. We further confirmed the presence of these three types of receptors by examining postsynaptic currents evoked by iontophoretic application of the three agonists, NMDA, (R,S)-alpha- amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA), and GABA. These results confirm that the dominant excitatory transmitter in the tectum appears to be glutamate. Furthermore, the retinotectal synapses (i.e., monosynaptic currents) express functional NMDA receptors that are voltage dependent and are not responsible for the bulk of normal excitatory transmission. Polysynaptic responses, however, are mediated by both non-NMDA and NMDA receptors, and inhibition plays a significant role in sculpting these polysynaptic responses.